Understanding the Role of Chemerin in the Pathophysiology of Pre-Eclampsia - Katarzyna Pankiewicz; Tadeusz Issat (MDPI AG, 2023)
Chemerin is a multifaceted adipokine that is involved in multiple biological processes, including inflammation, angiogenesis, adipogenesis, and energy metabolism, as well as oxidative stress. There is a vast body of evidence for a crucial role of chemerin in the development of different cardiovascular diseases. Blood chemerin levels, as well as its placental expression, are elevated in patients with pre-eclampsia (PE) and correlate positively with the severity of the disease. This narrative review summarizes the current knowledge about the potential role of chemerin during PE development, with a particular focus on its involvement in oxidative stress and endothelial dysfunction.